TINGKAT KENYAMANAN LINGKUNGAN BELAJAR SEKOLAH MENENGAH ATAS (SMA) NEGERI DI KOTA DENPASAR - Ambarawati, Ni Luh Gede; Arthana, Wayan; Suarna, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 1 (2016), 2016)
A healthy andcomfortable school environmentis necessary,besidessupporting the learning process, it can also improve student achievement. Noiseisdisturbingin the learning process, as well as theavailability offacilities and infrastructure will greatly affectthe comfort ofthe studentsinthe school. The purpose ofthis research is to determinethe comfort level ofstate senior highschoolstudyinthe city of Denpasarin termsofnoise levels, the availability andmanagement ofschool facilities and infrastructure and student perception against school envirumental level. The research methodused isdescriptivequantitativemethod. The locationof the research wasconductedin 8 State Senior High Schoolinthe city of Denpasar. Measurements ofnoise levelsateach schoolis capturedfromninesample pointsbyusing asound level meterand surveyof schoolfacilities and infrastructurethat are environmentally friendly. The comfort level of public high school learning environment in the city of Denpasar based on the level of noise has exceeded the qualty standard 55 dB, with the highest noise in the school yard of 73,0 dB, which motor vechicles as the main caused. Temperature and humidity do not affect the level of comfort, because they already meet the standards. Lighting of class room in eight public high school in the city of Denpasar very well. Because it meets the quality standard. Availability and management infrastructure is optimal and adequate to support mostly high school in the city of Denpasar. Support in the facilities and infrastructure have been seen in SMAN 3 Denpasar. Almost all students in eight high school in the city of Denpasar stated that the school environment is comfortable, even SMAN 3 Denpasar stated very comfotable at around 62,85 per cent.
Keywords: Noise, Infrastructure, SchoolLearning Environment